2010
DOI: 10.1016/j.epidem.2010.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Using the National Cattle Register to estimate the excess mortality during an epidemic: Application to an outbreak of Bluetongue serotype 8

Abstract: National Cattle Registers have been widely used to examine animal movements and their role in disease transmission, but less frequently for other epidemiological applications. Our study shows how routinely collected identification data can be used to evaluate the population impact of an epidemic in cattle and to derive an indirect estimate of the associated mortality. We adapted a method developed by Human health agencies, based on the modelling of historical mortality fluctuations, to analyze the evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 29 publications
1
42
0
1
Order By: Relevance
“…The levels of age-stratified cattle mortality are comparable to previous reports (Roy, 1990;Gardner et al, 1990;Karuppanan et al, 1997;Gulliksen et al, 2009;Thomsen et al, 2004Ortiz-Pelaez et al, 2008;McConnel et al, 2008;Maher et al, 2008;Perrin et al, 2010;Dechow and Goodling, 2008;Dechow et al, 2011;among others). For example, dairy cow mortality risks of 0.02-0.035 in Denmark 1990-1999(Thomsen et al, 2004), 0.048 in North America 2002(McConnel et al, 2008, mortality rates of 0.051-0.066 in Sweden 2002(Alvasen et al, 2012 have been reported.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The levels of age-stratified cattle mortality are comparable to previous reports (Roy, 1990;Gardner et al, 1990;Karuppanan et al, 1997;Gulliksen et al, 2009;Thomsen et al, 2004Ortiz-Pelaez et al, 2008;McConnel et al, 2008;Maher et al, 2008;Perrin et al, 2010;Dechow and Goodling, 2008;Dechow et al, 2011;among others). For example, dairy cow mortality risks of 0.02-0.035 in Denmark 1990-1999(Thomsen et al, 2004), 0.048 in North America 2002(McConnel et al, 2008, mortality rates of 0.051-0.066 in Sweden 2002(Alvasen et al, 2012 have been reported.…”
Section: Discussionsupporting
confidence: 89%
“…In consequence, a substantially increased mortality in a holding makes violated model assumptions likely. These may include welfare problems, insufficient health care or feeding practices, and infectious diseases like Bluetongue, FMD, and BSE (de Vries et al, 2013;Stevenson, 2003;Perrin et al, 2010). These and any other possibilities remain to be analyzed when examining mortality in a concrete deviant holding.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As other authors (Perrin et al, 2010;Barker et al, 2011;Dorea et al, 2013) we used weekly timescales to avoid the irregular weekday effect observed on the daily time series. Using the week as timescale brings stability into the models, however it also includes certain information bias and some timeliness reduction (Perrin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%